Emergency Smart Traffic Management based on WIFI Technology - Lahloh, Batool; Nassar, Samah (My University, 2018)
As the number of vehicle grows rapidly, traffic congestion problem increase as well.Because of this, emergency vehicles are delayed to reach the destination. Due to the above mentionable problem, control and management has become a major topic of modern traffic control system. So that we are going to build a wireless system called Emergency Smart Traffic Management system to reduce traffic congestion to successfully discharge missions and reduce the time required for their performance. This system is based on Bluetooth technology, which is characterized by low cost and availability in their phones. Our project will depend on Bluetooth technology which is going to be used as follow: The driver determines which route to use by using the control application that contains the four directions and then the Bluetooth cellular phone sends this information to the Bluetooth device located at the side of the traffic signal, Arduino uno kit will perform the check to ensure that information is received from the driver's side, If data is confirmed The Arduino Uno will start executing code commands accordingly depending on the situation that came from the driver. The path through which he is going is opened by turning the green light on that road and closing the rest of the path by activating the red light. When the emergency car passes, the dedicated button is pressed to return the traffic system to its normal state.